Listening to Images - Campt, Tina, 1964- (Book collections on Project MUSE., 2017)
Tina M. Campt explores a way of listening to photography by engaging with lost archives of state identification photographs of Afro-diasporan people taken between the late 1800s and the present, showing how to hear the quiet refusal emanating from these photos originally intended to dehumanize and police their subjects.